Desafios encontrados pelos produtores de fruticultura e hortaliças no assentamento 23 de Maio devido às mudanças climáticas - Pereira, Mércia Maria Damasio (Universidade Federal de São Carlos, 2024)
Studies related to climate change are gaining more notoriety, with the increase in deforestation caused by conventional agriculture and emissions of polluting gases into the Earth's atmosphere, the planet suffers a phenomenon called the intensified greenhouse effect, resulting in global warming. The consequence of which are extreme events, causing an imbalance in the rainfall regime, heat waves, hurricanes and desertification of some areas, such as equatorial areas. All of this is a major threat to food production for human beings, as these events directly affect the production system. The Landless Movement has sustainable production as one of its main objectives, so that it provides healthy food for the population and that its production has a low environmental impact. The present study aims to understand the cultivation methods and discuss the main difficulties faced with the extreme climatic conditions of the 23 de Maio Settlement, located in the Tupy District, a rural area belonging to the municipality of Itapetininga-SP. With this, five rural producers belonging to the settlement were interviewed. Everyone was able to answer the questions, and showed great concern about the extreme events that have been occurring in the region, especially droughts, which have been causing losses in their production, causing losses in some crops. Furthermore, these losses affect producers financially. Producers also noticed that there was a large increase in deforestation in permanent preservation areas (APPS) in a lagoon that belongs to the settlement. In addition, they highlight the lack of supervision and public policies that encourage sustainable cultivation in settlements.
Challenges found by fruit and vegetable producers in the 23 de Maio settlement due to climate change
Keywords: Agricultura familiar; Percepção; Produção; Orgânicos; Sustentabilidade; Family farming; Perception; Production; Organic; Sustainability; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA RURAL